COMPUTATIONAL THINKING SISWA AKUNTANSI DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS DAN KEMAMPUAN PEMECAHAN MASALAH - Safira Azzahra; Slamet Fauzan (Jurnal Pendidikan Ilmu Sosial, 2023)
Initially computational thinking was associated with informatics, even as a part of that field of science. However, according to different expert opinions, computational thinking can be incorporated into other fields of knowledge and real life. In addition, computational thinking is also still low for students at Vocational Schools majoring in accounting. Thus, computational thinking is a variety of knowledge and real-life areas that are influenced by critical thinking and problem-solving factors. The purposes of this research are (1) to find out whether there is an effect of critical thinking skills on computational thinking, (2) to find out whether there is an effect of problem-solving skills on computational thinking, and (3) to find out whether there is an effect of critical thinking skills and problem-solving skills. towards computational thinking. The research method used was a quantitative explanation. The sample used was convenience sampling, namely students majoring in accounting in Malang City. Methods of data collection using a questionnaire. Data analysis using multiple linear regression. The results of this study indicate that (1) Critical thinking skills had a significant positive effect on the computational thinking of students majoring in Accounting in Malang City. (2) Problem solving skills does not affect the computational thinking of students majoring in Accounting in Malang City. (3) Critical thinking skills and problem-solving skills effect simultaneously or jointly on the computational thinking of Accounting Department students in Malang City.